2016
DOI: 10.1111/eth.12534
|View full text |Cite
|
Sign up to set email alerts
|

Boldness, Dominance, and Territoriality in the Color Polymorphic Tree Lizard, Urosaurus ornatus

Abstract: Social dynamics in territorial species often reflect underlying variation in aggression and other aspects of social dominance among individuals. In ornate tree lizards (Urosaurus ornatus), males differing in dewlap color differ in social dominance: while blue males are the dominant, aggressive morph and always territorial, yellow males tend to exhibit a less‐aggressive satellite behavioral tactic. However, in habitats with fewer available territorial resources, yellow males defend territories and increase in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The isodar was straight over a wide range of densities and demonstrated that tree lizards preferred the wash habitat. Tree lizards are very territorial (Carpenter 1995, Taylor andLattanzio 2016), so we were expecting a curved isodar. It is possible that curvature in the isodar may only become apparent at very high densities, once the habitat is completely saturated with territories.…”
Section: Discussionmentioning
confidence: 98%
“…The isodar was straight over a wide range of densities and demonstrated that tree lizards preferred the wash habitat. Tree lizards are very territorial (Carpenter 1995, Taylor andLattanzio 2016), so we were expecting a curved isodar. It is possible that curvature in the isodar may only become apparent at very high densities, once the habitat is completely saturated with territories.…”
Section: Discussionmentioning
confidence: 98%
“…In lizards, male morphs differ in several traits including behaviour (Stephenson, 2010;Taylor & Lattanzio, 2016; Yewers, Pryke, & Stuart-Fox, 2016), morphology (Huyghe, Vanhooydonck, Herrel, Tadic, & Van Damme, 2007;Stephenson, 2010), territory (Zamudio & Sinervo, 2000), parasitic load (Megía-Palma et al, 2018) and physiology (LaDage, Riggs, Sinervo, & Pravosudov, 2009;Stephenson, 2010). However, different comparisons among morphs did not reveal any significant difference including morphometry (Meyers, Irschick, Vanhooydonck, & Herrel, 2006;Sacchi et al, 2007;Yewers, Jessop, & Stuart-Fox, 2017), total of number of offspring and their survivorship (Zamudio & Sinervo, 2000), performance (Huyghe et al, 2007;Meyers et al, 2006), behaviour, microhabitat use, thermoregulation (Huyghe et al, 2007) and/ or spermatogenic output (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Male polymorphisms have been reported in multiple genera within Phrynosomatidae including, but not limited to the following: Uta (Sinervo & Lively, 1996), Urosaurus (Taylor & Lattanzio, 2016) and Sceloporus (Rand, 1990). The Sceloporus genus is one of the most diverse genera of squamates (Wiens & Reeder, 1997) and exhibits a wide array of morphological variation, specifically sexually dimorphic characters (Jiménez-Arcos, Sanabria-Urbán, & Cueva del Castillo, 2017).…”
mentioning
confidence: 99%
“…Orange-throated males can be nomadic or sedentary, depending on resource levels (Moore et al, 1998), and do not defend territories (Moore et al, 1998). Males with yellow or green throats live in between the territories of blue-throated males and sneak copulations with females (Taylor & Lattanzio, 2016). Male throat colour is correlated with differences in aggression (Taylor & Lattanzio, 2016), diet (Lattanzio & Miles, 2016) and microhabitat use (Lattanzio & Miles, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Males with yellow or green throats live in between the territories of blue-throated males and sneak copulations with females (Taylor & Lattanzio, 2016). Male throat colour is correlated with differences in aggression (Taylor & Lattanzio, 2016), diet (Lattanzio & Miles, 2016) and microhabitat use (Lattanzio & Miles, 2014). Thus, testing for differences in habitat selection between male throat colour phenotypes will improve our ability to predict space use and will help determine whether habitat selection contributes to the maintenance of the throat colour polymorphism.…”
Section: Introductionmentioning
confidence: 99%